Handbook of Agri-Food Law in China, Germany, European Union Food Security, Food Safety, Sustainable Use of Resources in Agriculture - Härtel, Ines (Springer International Publishing : Imprint: Springer, 2018)
V, 657 p. 15 illus., 14 illus. in color.